Hubungan Penguasaan Sintaksis dan Morfologi Arab Terhadap Pemahaman Isi Teks-Teks Arab dalam Kitab Klasik di Pondok Pesantren Al-Mukhlisin Batu, Malang - Fahmi, Alif Anharul; Abidin, Munirul (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2023)
The aim of this research was to find out how the mastery of Arabic syntax and morphology relates to students' understanding of the contents of Arabic texts in the book at Al-Mukhlisin Islamic Boarding School, Batu City. This research is included in quantitative research because it uses statistical technique in the process of data analysis. The data collection for this research used a test instrument that was given to 25 students who were taken as a sample. Data analysis was performed using correlation to the collected data. The data consists of the independent variable, namely the mastery of Arabic syntax and morphology, and the dependent variable, namely the students' understanding of the contents of Arabic texts in the book at the Al-Mukhlisin Islamic boarding school in Batu City. The results of this study indicate that mastery of Arabic syntax and morphology has an influence of 86.4% on the ability to understand the contents of Arabic texts. The other 13.6% is influenced by other factors not discussed in this study, which are estimated to be in the form of vocabulary mastery, motivation, learning methods and models carried out in Islamic boarding schools, as well as other factors. In addition, the data stated that there was a strong correlation because it was known that p = 0.000 < 0.05 and the correlation coefficient value was 0.876.